2017
DOI: 10.1177/1363459317715777
|View full text |Cite
|
Sign up to set email alerts
|

Who or what has agency in the discussion of antimicrobial resistance in UK news media (2010–2015)? A transitivity analysis

Abstract: Who or what has agency in the discussion of antimicrobial resistance in UK news media (2010)(2011)(2012)(2013)(2014)(2015)? A transitivity analysis. AbstractThe increase of infections resistant to existing antimicrobial medicines has become a topic of concern for health professionals, policy makers and publics across the globe, however among the public there is a sense that this is an issue beyond their control. Research has shown that the news media can have a significant role to play in the public's understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…This observed focus on societal rather than individual responsibility is consistent with other reports (e.g. Evensen & Clarke, 2012;Collins, Jaspal & Nerlich, 2017). Certain facts that would be important for all citizens to know, such as the inefficiency of antibiotics toward viruses or the importance of completing a course of treatment as prescribed by the physician, were reported to a very low extent.…”
Section: Evolutionary Explanations For Antibiotic Resistancesupporting
confidence: 89%
See 1 more Smart Citation
“…This observed focus on societal rather than individual responsibility is consistent with other reports (e.g. Evensen & Clarke, 2012;Collins, Jaspal & Nerlich, 2017). Certain facts that would be important for all citizens to know, such as the inefficiency of antibiotics toward viruses or the importance of completing a course of treatment as prescribed by the physician, were reported to a very low extent.…”
Section: Evolutionary Explanations For Antibiotic Resistancesupporting
confidence: 89%
“…Bie, Tang and Treise (2016) compared the coverage of NDM-1 in Indian, British and American newspapers and found that reporting in the UK and US contained higher levels of dread (emotionally loaded words, infection consequences) and controllability (by providing personal protection measures) than the reporting in Indian newspapers. A study that applied a linguistic transitivity analysis to UK press concluded that no sense of individual responsibility was reported, but rather that the problem was directed to society as a whole (Collins, Jaspal & Nerlich, 2017).…”
Section: Newspaper Reporting On Antibiotic Resistancementioning
confidence: 99%
“…For England, we supplemented archival data of previous research conducted by the research team [6], [19], which resulted in 322 textual sources being retrieved and analysed for (a)-(c). We did not conduct analysis for media materials for England in this study, as this has been captured elsewhere in recent years [20], [21] with a frequency of reporting 'AMR'/'antibiotic resistance' and 'superbug' in the media averaging at up to 4.7 per month in popular and broadsheet newspapers between 2010-15 [22].…”
Section: (Ii) Assessment Of the Health Policy Settingmentioning
confidence: 99%
“…Indeed, the high prevalence of antibiotic resistance tends to correlate with low levels of public awareness about AMR [9]. Given the role of the media as the main source of information concerning health and science [5,10,11], understanding media conversations about antibiotics and AMR may be crucial for policymakers and public health experts when planning strategies to address this issue.…”
Section: Introductionmentioning
confidence: 99%